Bangsa Kanaan sebagai Kritik Ideologi terhadap Bangsa Israel Tafsir Yosua 11:16-23 - Heri Purwanto (Marturia, 2023)
AbstractThis interpretive article on the book of Joshua 11:16-23 aims to provide a reflection on the social and humanitarian events that have been full of acts of violence that have occurred recently. What is worse is that those who commit acts of violence and crimes against humanity are acting in the name of God's command and defending a particular religion. They